IMPROVING THE SEVENTH GRADE STUDENTS’ VOCABULARY MASTERY OF SMP ANASTASIA PANCUR BATU BY USING MAKE A MATCH TECHNIQUE - Simangunsong, Sonia Yohana; Pangaribuan, Jontra Jusat; Ginting, Fiber Yun Almanda (Kairos English Language Teaching Journal, 2022)
This research was primarily conducted to prove that the application of Make a Match technique could improve the seventh grade students of SMP Anastasia Pancur Batu and to describe their responses towards the application of Make a Match technique in the processes of learning vocabulary. This research is Classroom Action Research which was performed in two cycles. Each cycle consisted of three meetings. The quantitative data analysis showed that the students mean score increase continuously from 72,75 in pre test, 85,17 in formative test and 96,20. The qualitative data analysis showed that the students gave good responses towards the application of Make A Match technique. They felt more interested and encouraged to master vocabulary after Make a Match technique was applied. To sum up, the application of Make a Match technique could improve the students’ vocabulary mastery. It is advisable that English teachers should try applying Make a Match technique in teaching vocabulary.